Assessment of groundnut genetic diversity through DUS descriptor - Yasmine, F; Begum, M; Sikder, M R; Kamruzzaman, M; Sultana , M R; Rahman, M A (Bangladesh Journal of Nuclear Agriculture, 2025)
This study evaluated 33 groundnut (Arachis hypogaea L.) genotypes based on Distinctness, Uniformity, and Stability (DUS) guidelines using morphological traits. Significant variations were observed in key agronomic characteristics. Plant height ranged from 10.01 cm to 36.02 cm, with ICGV-5268 being the tallest. Plant width varied between 15.00 cm and 41.20 cm. Leaflet traits showed diversity, with Khenkhon having the longest leaflet (49.70 mm) and ICGV-93389 the widest (28.33 mm). Pod and seed dimensions also varied, with ICGV-1352 had the longest pods (36.70 mm) and ICGV-4514 the longest seed size (13.33 mm). Pod yield per plant ranged from 14.33 g to 48.86 g, with ISD-1314 exhibiting the highest yield potential. Qualitative traits indicated differences in growth habit, branching pattern, pigmentation, and leaflet morphology. Most germplasm displayed an erect growth habit (57.58%), while 30.30% were decumbent-3 type. Leaflet shape and margin characteristics further differentiated the genotypes. Cluster analysis grouped the genotypes into two main clusters, revealing genetic diversity. ICGV-5268, ISD-1314 and ICGV-4514 emerged as promising candidates for breeding due to their superior plant vigor, seed size, and yield potential. These findings highlight their importance as valuable genetic resources for groundnut improvement and breeding strategies. Bangladesh J. Nuclear Agric., 39(1): 1-12, 2025